Stabilizing zero-field skyrmions in Ir/Fe/Co/Pt thin film multilayers by magnetic history control - Petrović, Alexander Paul (2019)
We present a study of the stability of room-temperature skyrmions in [Ir/Fe/Co/Pt] thin film multilayers, using the First Order Reversal Curve (FORC) technique and magnetic force microscopy (MFM). FORC diagrams reveal irreversible changes in magnetization upon field reversals, which can be correlated with the evolution of local magnetic textures probed by MFM. Using this approach, we have identified two different mechanisms—(1) skyrmion merger and (2) skyrmion nucleation followed by stripe propagation—which facilitate magnetization reversal in a changing magnetic field. Analysing the signatures of these mechanisms in the FORC diagram allows us to identify magnetic “histories”—i.e., precursor field sweep protocols—capable of enhancing the final zero-field skyrmion density. Our results indicate that FORC measurements can play a useful role in characterizing spin topology in thin film multilayers and are particularly suitable for identifying samples in which skyrmion populations can be stabilized at zero field.